Roles of motor and cortical activity in sleep rebound in rat. (14th September 2020) - Wen, Yujun; Lv, Yudan; Niu, Jianguo; Xin, Christopher; Cui, Li; Vetrivelan, Ramalingam; Lu, Jun
Abstract: Sleep pressure that builds up gradually during the extended wakefulness results in sleep rebound. Several lines of evidence, however, suggest that wake per se may not be sufficient to drive sleep rebound and that rapid eye movement (REM) and non‐rapid eye movement (NREM) sleep rebound may be differentially regulated. In this study, we investigated the relative contribution of brain versus physical activities in REM and NREM sleep rebound by four sets of experiments. First, we forced locomotion in rats in a rotating wheel for 4 hr and examined subsequent sleep rebound. Second, we exposed the rats lacking homeostatic sleep response after prolonged quiet wakefulness and arousal brain activity induced by chemoactivation of parabrachial nucleus to the same rotating wheel paradigm and tested if physical activity could rescue the sleep homeostasis. Third, we varied motor activity levels while concurrently inhibiting the cortical activity by administering ketamine or xylazine (motor inhibitor), or ketamine + xylazine mixture and investigated if motor activity in the absence of activated cortex can cause NREM sleep rebound. Fourth and finally, we manipulated cortical activity by administering ketamine (that induced active wakefulness and waking brain) alone or in combination with atropine (that selectively inhibits the cortex) and studied if cortical inhibition irrespective of motor activity levels can block REM sleep rebound. Our results demonstrate that motor activity but not cortical activity determines NREM sleep rebound whereas cortical activity but not motor activity determines REM sleep rebound. Abstract : Sleep pressure increases gradually during the extended wakefulness and results in sleep rebound. In this study, we investigated the contribution of brain versus physical activities in rapid eye movement and non‐rapid eye movement sleep rebound by four sets of experiments. Our results demonstrate that prior motor activity determines non‐rapid eye movement (NREM) sleep rebound whereas prior cortical activity determines rapid eye movement (REM) sleep rebound.